Constrained variational response to Fock-space multi-reference coupled-cluster theory: Some pilot applications - Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Molecular Structure-Theochem, 2006)
Fock space (FS) multi-reference (MR) coupled-cluster (CC) has been established to be state-of-the-art method for energies of open-shell radicals, ionized, electron attached states and excited states. Due to the multi-root nature of the method, the linear response of MRCC, however, is non-trivial. Constrained variation approach (CVA) makes it plausible to calculate response of the MRCC method efficiently. However, the approach is used for only one root of the problem at a time. In the present article, we make first implementation of the approach and present test results of dipole moments of small radicals. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: constrained variation; coupled-cluster; Dipole moment; Multi-reference; response

Chemical shielding of closed-shell molecules using extended coupled-cluster theory - Ravichandran, Lalitha; Joshi, Sayali; Vaval, Nayana (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In this paper we report calculation of the nuclear magnetic shielding constant using extended coupled cluster response approach. We present the results for the HF, BH, CO and N(2) molecules. These results show importance of correlation corrections for the shielding constant.

Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.

Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.

Calculation of P,T-odd interaction constant of PbF using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2015)
The effective electric field experienced by the unpaired electron in the ground state of PbF, which is a potential candidate in the search of electron electric dipole moment due to some special characteristics, is calculated using Z-vector method in the coupled cluster single-and double-excitation approximation with four component Dirac spinor. This is an important quantity to set the upper bound limit of the electron electric dipole moment. Further, we have calculated molecular dipole moment and parallel magnetic hyperfine structure constant (A(parallel to)) of Pb-207 in PbF to test the accuracy of the wavefunction obtained in the Z-vector method. The outcome of our calculations clearly suggests that the core electrons have significant contribution to the ``atom in compound'' properties. (C) 2015 AIP Publishing LLC.

Calculation of hyperfine structure constants of small molecules using Z-vector method in the relativistic coupled-cluster framework - Sasmal, Sudip; Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Sciences, 2016)
The Z-vector method in the relativistic coupled-cluster framework is employed to calculate the parallel and perpendicular components of the magnetic hyperfine structure constant of a few small alkaline earth hydrides (BeH, MgH, and CaH) and fluorides (MgF and CaF). We have compared our Z-vector results with the values calculated by the extended coupled-cluster (ECC) method reported in Phys. Rev. A 91 022512 (2015). All these results are compared with the available experimental values. The Z-vector results are found to be in better agreement with the experimental values than those of the ECC values.

Correlation trends in the magnetic hyperfine structure of atoms: a relativistic coupled-cluster case study - Talukdar, Kaushik; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2018)
The role of electron correlation in the hyperfine structure of alkali metals and alkaline earth metal monopositive ions in their ground electronic configuration is investigated using the Z-vector method in a relativistic coupled-cluster regime within the singles and doubles approximation. The systematic effects of core-correlating functions, polarization of core electrons, and high-lying virtual functions on core electrons correlation are studied. The study reveals that the core-correlating function plays a significant role in core polarization and thus is very important for precise calculation of the wave function near the nuclear region. The inner-core electrons (1s-2p) require very high virtual energy functions for proper correlation. Therefore, the all-electron correlation treatment and the inclusion of higher-energy virtual functions are the key factors for precise calculation of the hyperfine structure constant of atoms. Our calculated values are in excellent agreement with the available experimental values, which also implies that the wave function produced by the Z-vector method is accurate enough for further calculation of the parity- and time-reversal symmetry-violating properties in atoms and molecules.

Charge transfer effect on relaxation mechanism in hydrated pyrrole-water systems following N-2s ionization - Kumar, Ravi; Bhattacharjee, Kankana; Ghosh, Aryya; Vaval, Nayana (ChemPhysChem, 2025)
This study investigates the relaxation mechanisms of pyrrole and pyrrole-water clusters (C4H5N-(H2O)n, where n=0-3 \${n = 0 - 3}\$ ) following N-2s ionization of pyrrole. Using various theoretical methods, we focus on the influence of water molecules and charge transfer on these non-radiative relaxation pathways. Our simulations included pyrrole solvated in 494 explicit water molecules equilibrated at 300 K and also employed a polarizable continuum model (PCM) to make the system more realistic and gain additional insights. In hydrated environments, the hydrogen bonding network between pyrrole and surrounding water molecules facilitates enhanced non-radiative relaxation pathways following inner valence ionization. Since these are hydrogen bonding systems, we have explored the possibility of proton transfer, which could occur in conjunction with other electronic decay processes.
Keywords: ab initio-calculations; auger decay; charge transfer; proton transfer; pyrrole